2021
DOI: 10.3390/pharmaceutics13040574
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Model Analysis of Supralingual, Oral and Intravenous Deliveries of Mycophenolic Acid

Abstract: Mycophenolic acid (MPA) is commonly used for organ rejection prophylaxis via oral administration in the clinic. Recent studies have shown that MPA also has anticancer activities. To explore new therapeutic options for oral precancerous/cancerous lesions, MPA was designed to release topically on the dorsal tongue surface via a mucoadhesive patch. The objective of this study was to establish the pharmacokinetic (PK) and tongue tissue distribution of mucoadhesive MPA patch formulation after supralingual administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…The OXP patch may lead to a burst release within the first 1 h followed by a long-term sustained release [20]. In addition, our previous study on drug mycophenolic acid showed relatively lower plasma exposure in systemic circulation and higher accumulation in tongue tissue after supraglingual administration, suggesting that supralingual patch delivery may provide the benefits of longer drug accumulation in the tongue tissues and less systemic exposure [29]. Several drug dosage formulations have been reported for intraoral application, including the implantable tablet, mucoadhesive patch, film, microsphere, ointment, cream, and hydrogel [30][31][32][33][34][35].…”
Section: Pharmacokinetics and Tongue Distribution Studymentioning
confidence: 92%
“…The OXP patch may lead to a burst release within the first 1 h followed by a long-term sustained release [20]. In addition, our previous study on drug mycophenolic acid showed relatively lower plasma exposure in systemic circulation and higher accumulation in tongue tissue after supraglingual administration, suggesting that supralingual patch delivery may provide the benefits of longer drug accumulation in the tongue tissues and less systemic exposure [29]. Several drug dosage formulations have been reported for intraoral application, including the implantable tablet, mucoadhesive patch, film, microsphere, ointment, cream, and hydrogel [30][31][32][33][34][35].…”
Section: Pharmacokinetics and Tongue Distribution Studymentioning
confidence: 92%